Geo-Portal Implementation with a Combined Approach of AHP and SWOT - Mousavi, Zahra; Behzadi, Saeed (International Journal of Natural Sciences Research, 2019)
In order to achieve the goals of sustainable development, reliable and more quality spatial data is required in the decision-making and planning process. In other words, the existence of an appropriate infrastructure of spatial data is necessary for the sustainable development of the community. Recently, the creation of a Spatial Data Infrastructure (SDI) is in the program of many states at various national, provincial and local levels. SDI can be defined from a variety of perspectives; however, the geoportal design and implementation play a key role as a platform for providing spatial services. In this regard, various software exists as a geoportal platform, which is a necessity to choose an appropriate software tool among them. To achieve this goal, a set of related software products should be investigated and compared. Then, the criteria that are important from the perspective of the user and the developer are selected for software comparison, and ultimately software packages which support SDI (for geo-portal) are selected. In this regard, attempts to select one software with emphasis on environmental activities among four open source software for geo-portal implementation. In this article, the combination of AHP and SWOT is used to achieve this goal with an emphasis on environmental activities. Therefore, the criteria are first weighed using the AHP method, then, the SWOT method is used to select the appropriate software based on identifying strengths, weaknesses, opportunities, and threats.